The effect of voluntary termination of pregnancy on female sexual and emotional well-being in different age groups - Erika Limoncin; Angela D'Alfonso; Claudia Corallino; Vincenza Cofini; Giovanna Di Febbo; Giacomo Ciocca; Daniele Mollaioli; Felice Patacchiola; Emmanuele A. Jannini; Gaspare Carta (Taylor & Francis Group, 2017)
Introduction: To evaluate the impact of voluntary termination of pregnancy (VTOP) on the psycho-sexological well-being of females before/six months after the abortion. Methods: A sample of 194 women was recruited from three obstetrics and gynaecological divisions. The women were evaluated for the variables "sexual functioning" with the Female Sexual Function Index (FSFI), "depression" with the Beck Depression Inventory (BDI-II), and "anxiety state" with the Self-Rating Anxiety Scale (SAS) at time 0 (the beginning of the abortion procedure) and time 1 (six months after the abortion). Since 24 women refused to fill out the questionnaires, the final sample was composed of 170 women. Results: The women showed a slight although significant improvement in the mean FSFI score from time 0 (16.7 ± 12.9) to time 1 (20.9 ± 13.8) (p < 0.001) which paralleled with a slight decrease in the incidence of clinically significant sexual dysfunction [49% (84/170) (time 0) versus 34.1% (58/170) (time 1)], (McNemar's test; p = 0.0241). The sub-group of younger women (18-25) showed a lesser increase in FSFI score from time 0 to time 1. In addition, both depression (p = 0.048) and anxiety (p < 0.001) significantly decreased over time. However, the female sexuality remained impaired since more than two thirds (69.5%) of women were sexually dysfunctional six months after VTOP. Discussion: Voluntary TOP may influence the sexuality of younger females differently from how it influences that of older women. Hence, the sexuality of younger female should be regularly supervised in follow-up examinations.